International Congress on Health in Arbaeen; to strengthen inter-departmental coordination and synergy to reduce the obstacles in providing health services to the pilgrims - Mulazim Hussain Bukhari; Muhammad Ali Kumail (Journal of the Pakistan Medical Association, 2023)
The 3rd international congress on Arbaeen in health was a significant event held from 2nd to 4th August, 2023 in Tehran, Iran. It brought together experts and scholars from nine countries to discuss and exchange knowledge on health-related issues during the Arbaeen pilgrimage. This congress provided a platform to explore innovative approaches, research findings, and best practices in promoting health and well-being among Arbaeen pilgrims. It also facilitated networking and collaboration among healthcare professionals, researchers, and policymakers, leading to the development of effective strategies for ensuring the health and safety of the millions of pilgrims participating in the Arbaeen pilgrimage. This congress will play a crucial role in advancing healthcare practices and enhancing the overall pilgrimage experience. The Arbaeen pilgrimage, which is one of the largest religious gatherings in the world, takes place 40 days after Ashura, the martyrdom anniversary of Imam Hussain (AS), the third Imam of Shia Muslims, and the grandson of Prophet Muhammad (PBUH). Each year, a huge crowd of people flock to Karbala, where the holy shrine of Imam Hussein (AS) is located, to perform mourning rituals. This year Arbaeen was on September 6,2023. Keywords: Arbaeen, Congress, Health, Hilal e Ahmar, Karbala, Imam e Hussain, Pilgrim